Pelatihan Pembelajaran Fisika Pelatihan Pembelajaran Fisika GASING untuk Guru IPA SMP untuk Mengatasi Kesulitan Belajar Fisika - Murni, Murni; Fajarudin, Fauji (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
Physics is seen as a difficult subject for students. This assumption is often associated with the teacher's lack of ability to teach Physics. The purpose of this community service activity is to training physics to Junior High School science’s teacher using GASING method. The activity was attended by 51 science teachers that teachers are divided into 3 classes. This activity took place on 21st – 25th October 2019 at PMI office, Serang Regency. The concept taught to teacher are Magnitude and Units, Motion, Force, Work and Energy, and Pressure. Before and after learning, the training participants were given a test in the form essay. The data of community service were analysis using normalize gain (N-gain) and Wilcoxon’s test. The results of N-Gain, it was obtained that there was an increase by 0.55 with a medium category. And the result of Wilcoxon’s test show that the significance value is 0.00 < 0.05, which means that there is a significance increase in cognitive ability of junior high school science’s teacher after receiving training.